Clinicopathological characteristics, diagnosis and treatment of melanoma in Serbia – the Melanoma Focus Study - Kandolf-Sekulović, Lidija; Babović, Nada; Jokić, Neven; Balić, Mirjana; Nikolin, Borislava; Nikolić, Dejan; Janjić, Zlata; Mijušković, Željko; Rajović, Milica; Novaković, Marijan; Vrbić, Svetislav; Pejčić, Ivica; et al. (Vojnosanitetski pregled, 2015)
Background/Aim. Treatment options for metastatic melanoma in Serbia are limited due to the lack of newly approved biologic agents and the lack of clinical studies. Also, there is a paucity of data regarding the treatment approaches in different tertiary centers and efficacy of available chemotherapy protocols. The aim of this study was to obtain more detailed data about treatment protocols in Serbia based on structured survey in tertiary oncology centers. Methods. Data about the melanoma patients treated in 2011 were analyzed from hospital databases in 6 referent oncology centers in Serbia, based on the structured survey, with the focus on metastatic melanoma patients (unresectable stage IIIC and IV). Results. A total of 986 (79–315 in different centers) patients were treated, with 320 (32.45%) newly diagnosed patients. There were 317 patients in stage IIIC/IV, 77/317 aged < 50 years. At the time of diagnosis 47.3% of patients were < 60 years of age (24.2% < 40 years, 23% 50–59 years, 52.6% > 60 years). At initial diagnosis 12.5% of patients were in stage III and 4.5% in stage IV. The most common type was superficial spreading melanoma (50–66%), followed by nodular melanoma (23.5–50%). Apart from the regional and distant lymph node metastases, the most frequent organs involved in stage IV disease were distant skin and soft tissues (12–55%), lungs (19–55.5%), liver (10–60%), and bones (3–10%). The first line therapy in stage IV metastatic melanoma was dacarbazine (DTIC) dimethyl-triazeno-imidozole-carboxamide in 61–93% of the patients, while the second line varied between the centers. Disease control (complete response + partial response + stable disease) was achieved in 25.7% of the patients treated with the first line chemotherapy and 23.1% of the patients treated with the second line therapy, but the duration of response was short, in first-line therapy 6.66 ± 3.36 months (median 6.75 months). More than 90% of patients were treated outside the clinical trials. Conclusion. Based on this survey, there is a large unmet need for the new treatment options for metastatic melanoma in Serbia. The development of national guidelines, and greater involvement in international clinical studies could lead to widening of treatment options for this chemotherapy resistant disease.